Religious Character Building through Cultural Acculturation: An Ethnographic Study of Islamic Ritual Traditions in Tangerang - Siti Munawati (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2026)
The relationship between Islamic teachings and local cultural traditions provides an important context for understanding how religious character is developed within contemporary communities. This study examines how cultural acculturation through Islamic ritual traditions contributes to religious character formation and social cohesion in Tangerang, Indonesia. A qualitative ethnographic design was employed to explore the meanings, practices, and social interactions surrounding syukuran kehamilan, aqiqah, haul, and tahlil. Data were obtained through participant observation, semi-structured interviews, document analysis, and field notes involving religious leaders, community elders, cultural practitioners, neighborhood leaders, and local residents. The data were analyzed through data reduction, coding, thematic categorization, data display, and conclusion drawing, while source and method triangulation, prolonged engagement, and member checking were used to strengthen trustworthiness. The findings indicate that these traditions function not only as religious ceremonies but also as informal spaces for learning and practicing gratitude, responsibility, empathy, generosity, cooperation, and mutual respect. Their repeated participation also facilitates intergenerational transmission of Islamic values, strengthens interpersonal trust and solidarity, and supports harmonious relationships within the multicultural community. The study further develops an initial Community-Based Character Education Model linking Islamic values, cultural acculturation, ritual participation, religious character formation, and social cohesion. These findings highlight the potential of culturally embedded religious traditions as complementary educational resources for sustaining religious character and community harmony.